The Implementation of Zoom Meeting Utilization in Improving the Quality of Student Learning - Angkat, Jungga Ganda Tungga; Angkat, Jonggi Ganda Tua; Kwadkew, Theranan (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the implementation of Zoom Meeting utilization in improving the quality of student learning. The research method used is a qualitative approach with a descriptive study design. The subjects of this study include teachers and students involved in the online learning process. Data collection techniques were conducted through observation, interviews, and documentation. The results show that the use of Zoom Meeting can enhance interaction between teachers and students, facilitate direct delivery of learning materials, and provide flexibility in the learning process. In addition, features such as screen sharing, breakout rooms, and recorded sessions support the effectiveness of learning. However, several challenges were identified, including limited internet connectivity and insufficient technological readiness among some students. Therefore, appropriate strategies are needed to optimize the use of Zoom Meeting to continuously improve the quality of learning.